The role of English teachers in creating learning environments for preschoolers. (2024)
This study explores how learning environments can promote English oral interaction in early education settings, focusing on the context of preschool grades. Employing documentary analysis. Several case studies from different countries of America were examined alongside insights from theorists like Vygotsky (1978, 2007), Montessori (1949, 2013, 2021) , Krashen (1998, 2019), and Reggio Emilia (2006,2019). Teaching practices and strategies were analyzed to address the research question: How can learning environments facilitate English oral interaction among preschoolers? Findings revealed the crucial role of teachers in creating supportive environments and the significance of tailored spaces and materials for language instruction. Strategies such as dialogue-based activities and language- rich environments were identified as effective in promoting oral interaction. However, limitations included the lack of specific language policies for preschool education in Colombia, and recommendations for future research advocates for empirical studies to validate teaching strategies and explore the impact of technology. Overall, the study underscores the importance of creating conducive learning environments to foster preschoolers' language acquisition and social development.